Students’ Knowledge, Attitudes, and Practices Regarding Environmental Education among Intermediate-Level Students - Nasim, Ammara; Khushnood Iftikhar, Sidra (JSE, 2025)
The environment is the backbone of human existence, and its protection is not an option but a dire need that has serious long-lasting implications on the lives of human being. The study is significant as the unprecedented environmental changes ponders to plan and immediate implementation of recommended actions to protect environment which demands evaluation of awareness level, attitude and practices. Thus, the present descriptive study was intended to evaluate the knowledge, attitude and practices regarding environmental education in the case of students at the intermediate level in government colleges across the country. In line with the deductive approach, the present study proposed the KAP instrument with the use of the Palmer’s framework, which included three major elements: knowledge of, attitude towards, and practice relating to the environment. The validity of the instrument was ensured through the experts’ opinion. The reliability of the instrument was ensured through internal consistency, which was calculated using Cronbach’s Alpha, yielding a value of 0.816. A convenience sample has been obtained through an online survey, which has been prepared using Google Forms. The findings of this study specify that the learners were found to consider the environment in their lifestyles with a mean overall score entailing the category of being moderate, though the real practice of responsible environmental practices was low. It is hereby recommended to integrate more practical, action-based aspects into environmental education in schools at the intermediate level in Pakistan.